2014
DOI: 10.1074/jbc.m113.491217
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal Hydrophobic Amino Acids of Activating Transcription Factor 5 (ATF5) Protein Confer Interleukin 1β (IL-1β)-induced Stabilization

Abstract: Background:The N-terminal region of ATF5 is responsible for its CdCl 2 -and NaAsO 2 -induced expression. Results: IL-1␤ stabilizes ATF5 protein and elevates the translation efficiency of ATF5 mRNA. Conclusion:The N-terminal hydrophobic amino acids of ATF5 are important for protein stabilization and responsiveness to IL-1␤. Significance: This study provides new insights about the roles of ATF5 in immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…Recently, it has been demonstrated that the N-terminal amino acids of ATF5 are important for IL-1␤-induced ATF5 stabilization, which is mainly controlled by proteasome-mediated proteolysis (31). Similarly, in our experiments, we found that the N-terminal residues of ATF5 conferred NLK-induced stabilization, which was significantly blocked by proteasome inhibition.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Recently, it has been demonstrated that the N-terminal amino acids of ATF5 are important for IL-1␤-induced ATF5 stabilization, which is mainly controlled by proteasome-mediated proteolysis (31). Similarly, in our experiments, we found that the N-terminal residues of ATF5 conferred NLK-induced stabilization, which was significantly blocked by proteasome inhibition.…”
Section: Discussionsupporting
confidence: 67%
“…The asterisks indicate a significant difference (P Ͻ 0.05) calculated by one-way analysis of variance followed by Tukey's multiple-comparison test. (31). Accordingly, truncated ATF5 was overexpressed with NLK to determine whether the N-terminal residues were required for the NLK-mediated stabilization of ATF5.…”
Section: Nlk Activates the C/ebp Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of transgenes was induced with dox 24 h after transfection of MEFs and protein expression was detected after 48 h by western blot analysis. Consistent with expression in HEK293T cells ( Figure 1A) Hydrophobic N-Terminal Non-native Amino Acids Cause Proteasomal Degradation of KLF4 S Because a hydrophobic N-terminus can impair protein stability (Abe et al, 2014), we evaluated the hydrophobicity of the N-terminus for each KLF4 variant ( Figures S2A and S2B). The first nine N-terminal amino acids of KLF4 L encode mostly hydrophilic residues, while the N-terminus of KLF4 S was found to be mainly hydrophobic ( Figure S2A, right).…”
Section: Additional Non-native N-terminal Amino Acid Residues Impairsmentioning
confidence: 72%
“…In the P-N-end rule, [P] and also penultimate residues are involved in recruitment of the GID ubiquitin ligase subunit GID4, while adjacent [E] residues are prone to escape from the recognition (Chen et al, 2017). The principle of these rules is still not fully understood, but hydrophobicity of N-terminal residues is one of the regulatory factors in the protein stability (Abe et al, 2014). Consistent with these previous reports, we found an enhanced hydrophobicity at the N-terminus of KLF4 S suggesting that addition of [P] and [PL] triggers its proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%